2015
DOI: 10.29252/ijrm.13.12.793
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor gene variants with polycystic ovary syndrome: A case control study

Abstract: Background: Vitamin D and insulin play an important role in susceptibility to polycystic ovary syndrome (PCOS), and therefore vitamin D receptor (VDR), parathyroid hormone (PTH), and insulin receptor (INSR) gene variants might be involved in the pathogenesis of PCOS. Objective: The present study was designed to investigate the possible associations between polymorphisms in VDR, PTH, and INSR genes and the risk of PCOS. Materials and Methods: VDR, PTH, and INSR gene variants were genotyped in 35 women with PCOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Subgroup analysis based on the ethnicity of the study group was performed to detect any relationship between VDR gene ApaI polymorphism and PCOS risk. Then, we conducted a subgroup analysis stratified by population of the association of the VDR gene ApaI polymorphism and PCOS risk from 7 case-control studies, [20][21][22][23][24][25][26] as pooling of the data from individual studies has the advantage of reducing random errors. Also, most of the included studies scored 5 or more stars in NOS quality assessment score criteria and suggested good to moderate quality by clearly stating the sample size, genotype, inclusion criteria of patients, and characteristics of healthy controls.…”
Section: Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroup analysis based on the ethnicity of the study group was performed to detect any relationship between VDR gene ApaI polymorphism and PCOS risk. Then, we conducted a subgroup analysis stratified by population of the association of the VDR gene ApaI polymorphism and PCOS risk from 7 case-control studies, [20][21][22][23][24][25][26] as pooling of the data from individual studies has the advantage of reducing random errors. Also, most of the included studies scored 5 or more stars in NOS quality assessment score criteria and suggested good to moderate quality by clearly stating the sample size, genotype, inclusion criteria of patients, and characteristics of healthy controls.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…[18][19][20] Considering the past establishment of the important functions of VDR gene ApaI polymorphism, many studies have explored the association between VDR gene ApaI polymorphism and PCOS risk. [20][21][22][23][24][25][26] However, individual studies yielded inconsistent and even conflicting results. This may be attributed to limited sample sizes and inadequate statistical power, which might affect their reliability.…”
Section: Introductionmentioning
confidence: 99%
“…VDR ApaI 46,47 and BsmI gene 47 polymorphisms were associated with an increased risk of PCOS, after adjustment of results for age and body mass index (BMI). By contrast, other studies failed to find any association of these variants with PCOS susceptibility.…”
Section: (B) Vdr Gene Polymorphisms and Pcosmentioning
confidence: 99%
“…Wehr and coworkers (21) reported no significant influence of genetic variations and PCOS susceptibility, but VDR and Vit D level-related variants were shown to be associated with some dis-orders in PCOS including Vit D levels. Mahmoudi and coworkers (22) reported that the ApaI (rs7975232) genotype »AA« could be considered as a marker of decreased susceptibility for PCOS, while the »aa« genotype was associated with an increased risk for PCOS. Mcgrath et al (23) showed that there was a significant relationship between rs10735810 (merged with rs2228570) and levels of Vit D, and the T allele was associated with higher concentrations of Vit D. In contrast, Bagheri et al (24) reported no statistically significant association with PCOS susceptibility.…”
Section: Introductionmentioning
confidence: 99%